A silogística categórica dos analíticos anteriores de Aristóteles - Rasch, Elton Luiz (2013)
The present dissertation provides a reconstruction of the categorical part of Aristotle s (384 BC 322 BC) syllogistic, from the standpoint of the theory given in Prior Analytics, a piece of the Organon. Throughout the work it will be explained the methods which Aristotle has proposed to give support to his theory, many of them suffering only occasional changes to the present days. So, on one hand, this demonstrates the relevance of syllogistic on heuristic respects, and on the other, it shows that modern logic inherited much from Aristotle s one - either by abandonment or improvement of parts of his theory, either by embedding their methods in more refined formal structures. Initially, I ll give an overview of the theory and its relation to the epistemology proposed by Aristotle, as well as the assumptions derived from his metaphysics. Next, the operation of the methods used to prove Aristotle s theory will be demonstrated. Finally, an heuristics for the theory will be outlined, also proposed by Aristotle himself. Evidently, it is not intended to argue that Aristotle's logic is suitable for scientific research nowadays, as it seems to have been conceived at the time of its emergence and rise. However, through this research it is possible to note that the simplicity behind the syllogistic theory gives us a relatively underrated power today, especially by the emergence of modern logic.